Pelaksanaan Layanan Bimbingan dan Konseling di Sekolah Menengah Atas Negeri (SMAN) 4 Kerinci - Permana, Satya Anggi; Syahniar, Syahniar; Daharnis, Daharnis (Konselor, 2014)
SMAN 4 Kerinci (Senior High School) is one of favorite schools which has potential to conduct guidance and counseling service optimally. This is supported by its conducive condition and the sufficient number of the teachers. All of the teachers have qualification in Guidance of Counseling education. In addition, this school has adequate facilities. Unfortunately, the phenomena in the field indicated that the guidance and counseling service was not effectively conducted. This research was intended to describe the implementation of Guidance and Counseling service in that school. This was a qualitative research which applied phenomology approach. The informants of the research were the school fellows including headmaster, vice headmaster, guidance and counseling teachers, subject teachers and classroom teachers. The data where collected through observation, interview and documentation study. To check the trustwortiness of the data, there were four conducted (1) credibility, (2) transferability, (3) depedability, and (4) conformability. The data gathered where analyzed by (1) data reduction, (2) displaying the data and, (3) drawing conclusion/verifying. The research findings showed that the Guidance and Counseling service was not yet conducted optimally at SMAN 4 Kerinci. The cooperation between Guidance and Counseling Teachers with other school fellows was not yet established. This research concluded that the conducive atmosphere, the availability of sufficient qualified teachers, the adequate number of school fellows and the availability of sufficient facilities unless they were supported by good cooperation among related parties, the Guidance and Counseling service would not be optimally accomplished. Based on these conclusions, it was suggested: (1) the Guidance and Counseling teachers to be professional in carrying out their duties and responsibility and to be albe to cooperate with other school fellows. and (2) the school fellows to understand their roles in implementing Guidance and Counseling activities at school and be albe to get involved actively in.